PENGGUNAAN PUPUK KANDANG TERHADAP EFEKTIFITAS Trichoderma viride UNTUK MENGENDALIKAN PENYAKIT LAYU FUSARIUM PADA TANAMAN TOMAT - Asniah, Asniah; Khaeruni, Andi; Anwar, Hasniar (Jurnal Agroteknos, 2012)
Fusarium oxysporum is one of the important pathogens that causes disease in many crops, especially horticulture crops, one of which causes Fusarium wilt disease in tomato plants . The purpose of this study was to evaluate the use of manure on the effectiveness of Trichoderma viride to control fusarium wilt disease on tomato plants. Manure used was cow and chicken manure, applied before and after planting. The research design was completely randomized design (CRD) with 9 (nine) treatment and 3 replicates. The treatments were without the application of manure and T. viride (A) , without manure but with T . viride before planting (B), without manure but with T. viride applied after planting (C), chicken manure without T. viride (D), chicken manure and T. viride application before planting (E), chicken manure and T. viride application after planting (F), cow manure without T. viride (G), cow manure and T. viride application before planting (H), cow manure and application of T. viride after planting (I). The results showed that chicken manure and T. viride application before planting were effective in reducing the incidence and severity of Fusarium wilt disease on tomato plants. The incidence and severity of disease was at 20 % and 26.67 % , respectively. Keyword: manure, tomato plants, Trichoderma viride